2013
DOI: 10.1071/ch13276
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Secondary Structure on Electron Transfer in Peptides

Abstract: A series of synthetic peptides containing 0-5 a-aminoisobutyric acid (Aib) residues and a C-terminal redox-active ferrocene was synthesised and their conformations defined by NMR and circular dichroism. Each peptide was separately attached to an electrode for subsequent electrochemical analysis in order to investigate the effect of peptide chain length (distance dependence) and secondary structure on the mechanism of intramolecular electron transfer. While the shorter peptides (0-2 residues) do not adopt a wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Circular dichroism and NMR analysis reveals that the backbone of folds into a 3 14 -helical structure, which is consistent with geometry optimization 21,24 using the density functional theory (DFT) method. Calculations for 1 suggest that it adopts an ill-defined conformation.…”
Section: Electron Transfer Dynamics: Superexchange Vs Hoppingsupporting
confidence: 72%
“…Circular dichroism and NMR analysis reveals that the backbone of folds into a 3 14 -helical structure, which is consistent with geometry optimization 21,24 using the density functional theory (DFT) method. Calculations for 1 suggest that it adopts an ill-defined conformation.…”
Section: Electron Transfer Dynamics: Superexchange Vs Hoppingsupporting
confidence: 72%
“…Electron transfer in proteins plays an important role in a wide range of metabolic processes at the cellular level. 1 , 2 Many factors have been shown to influence this electron transfer, including the distance separating the electron donor and acceptor, 3 5 the extent of secondary structure, 6 , 7 dipole moment, 8 10 and the nature of the constituent amino acid side chains. 11 14 Of particular significance is the suggestion that peptides can undergo electron transfer via either a bridge-assisted superexchange or an electron hopping mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Figure 4 a, the dependence is not linear; this was explained by the authors as observing the hopping mechanism (existing theoretical models for ET are discussed in Section 5). Evidence for the importance of the secondary structure, and subsequently, the amount of hydrogen bonds, for efficient ET across the α helix was reported by Abell and co‐workers,62 who followed electrochemical ET across a poly‐Aib peptide. They observed that the dependence of the ET rate on the distance between Fc and the electrode became very shallow, only after the formation of the helical structure, whereas in very short peptides, in which the helical structure cannot be formed, this dependence is very steep (Figure 4 b).…”
Section: Electrochemically Induced Etmentioning
confidence: 92%